Comparison of PCR-based diagnoses for visceral leishmaniasis in Bangladesh - Khan, Md. Gulam Musawwir; Bhaskar, Khondaker Rifat Hasan; Kikuchi, Mihoko; Salam, Md. Abdus; Akther, Tania; Haque, Rashidul; Mondal, Dinesh; Hamano, Shinjiro (Elsevier, 2014)
The diagnosis of visceral leishmaniasis (VL) is performed using multiple methods encompassing parasitological, serological and nucleic acid-based diagnostic tools, each method with its own unique advantages and disadvantages. Conventional parasitologicalmethods are risky for the patient and require skilled personnel to collect specimens from spleen or bone marrow, and hence they are not generally available in impoverished areas. Polymerase chain reaction (PCR) has been validated as an excellent alternative to microscopy in terms of sensitivity and specificity. Here, we evaluate four different PCR assays targeting ITS1, ITS2, mini-exon and small subunit-rRNA (SSUrRNA) using DNA extracted from peripheral blood buffy coat in order to avoid more invasive processes. A total of 61 VL patients and 75 non-VL infected control individuals were enrolled. The VL patients were confirmed to be positive for Leishmania amastigotes in splenic smears by microscopy. Sensitivities of the PCR targeting ITS1, ITS2, SSUrRNA and mini-exon were 96.7%, 91.8%, 88.5% and 34.4%, respectively, while the specificity was 98.7% for all methods. Nested PCR for ITS1 resulted in 100% sensitivity. The efficacy of each PCR was evaluated with various Leishmania amastigote parasite loads in each spleen smear, graded from 1+ to 5+. The PCR targeting ITS1 showed 100% sensitivity for the detection of Leishmania donovani in all samples from grades ≥3, ≥4, and ≥5, respectively. The restriction fragment length polymorphism observed in ITS1 amplicons digested by HaeIII classified the parasite into L. donovani complex. The ITS1 PCR was found to be equal to conventional, but very invasive and risky parasitological diagnoses and superior to other PCR based methods in sensitivity and examination of genetic heterogeneity. We recommend the PCR targeting ITS1 using peripheral blood buffy coat DNA as an alternate, less invasive diagnostic choice for the confirmation of L. donovani infection.